New Records and List of Genera of Braconidae (Hymenoptera: Ichneumonoidea) at the University of Zulia Museum of Arthropods, Venezuela - Quirós, Magally; Petit, Yadira; Marsh, Paul (Boletín del Centro de Investigaciones Biológicas, 1970)
We examined about 23,000 specimens of Braconidae from Venezuela, deposited at the Museo de Artrópodos de la Universidad del Zulia (MALUZ), located in Maracaibo, Zulia State, Venezuela. The braconids were collected during several research projects and field visits, from 1961 to 2005. Identification was done chiefly by Paul Marsh (Systematic Entomology Laboratory (SEL), United States Department of Agriculture (USDA) and Rosa Briceño (Universidad Centro Occidental Lisandro Alvarado (UCLA), Venezuela, and among 13 subfamilies, 35 genera and 59 species counted, 11 genera are new records for Venezuela. Collection information (state, year, locality) as well as number of species and specimens is given for each genus. This information will help better the taxonomic and biogeographical knowledge of this family of parasitic wasps.